2021
DOI: 10.1126/sciadv.abd5835
|View full text |Cite
|
Sign up to set email alerts
|

An inverse-breathing encapsulation system for cell delivery

Abstract: Cell encapsulation represents a promising therapeutic strategy for many hormone-deficient diseases such as type 1 diabetes (T1D). However, adequate oxygenation of the encapsulated cells remains a challenge, especially in the poorly oxygenated subcutaneous site. Here, we present an encapsulation system that generates oxygen (O2) for the cells from their own waste product, carbon dioxide (CO2), in a self-regulated (i.e., “inverse breathing”) way. We leveraged a gas-solid (CO2–lithium peroxide) reaction that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 61 publications
(94 reference statements)
0
37
0
Order By: Relevance
“…Inadequate oxygenation at subcutaneous space is another factor limit the viability of transplanted islets. Recently, Wang et al demonstrated that Inverse breathing Encapsulation Devise (iBED), a silicon-based gas exchangeable materials improves oxygen (O 2 ) delivery is encapsulated islets and shows prolonged survival in multiple xenograft models (88). Challenge of transplantation of these islets with macro-and micro-encapsulation methods at subcutaneous sites still remain present as more islets (>2-5 times) are required to achieve normal glycemia with devices compared to naked transplantation.…”
Section: Subcutaneous Space Transplantation Sitementioning
confidence: 99%
“…Inadequate oxygenation at subcutaneous space is another factor limit the viability of transplanted islets. Recently, Wang et al demonstrated that Inverse breathing Encapsulation Devise (iBED), a silicon-based gas exchangeable materials improves oxygen (O 2 ) delivery is encapsulated islets and shows prolonged survival in multiple xenograft models (88). Challenge of transplantation of these islets with macro-and micro-encapsulation methods at subcutaneous sites still remain present as more islets (>2-5 times) are required to achieve normal glycemia with devices compared to naked transplantation.…”
Section: Subcutaneous Space Transplantation Sitementioning
confidence: 99%
“…The reaction of CO 2 -lithium peroxide from an aqueous cellular environment by a gas-permeable membrane yielded a device that supported functional islets in retrieved mice for more than 2 months (L.H. Wang et al, 2021 ).…”
Section: Hydrogel-based Encapsulation Devicesmentioning
confidence: 99%
“…Encapsulation systems such as the TheraCyte macroencapsulation device system, enable protection of the grafts from host immune cell infiltration via a physical barrier (112)(113)(114)(115)(116). A gas exchangeable enhanced O2 supply device has been developed to aim for enhancing the graft survival (117)(118)(119). This macroencapsulation device system is being utilized in an ongoing clinical trial of stem cell-derived pancreatic progenitor cells or primary human islets in T1D patients (116,118).…”
Section: Immune Protection By Immunosuppressants and Macro/ Micro Encapsulation Devicementioning
confidence: 99%